Clinical application of fetal Nuchal Translucency combined with noninvasive prenatal testing in screening chromosome abnormalities - Guangzhen Fu; Shuang Hu (PLoS ONE, 2026)
Objective To explore the clinical application of fetal nuchal translucency (NT) combined with noninvasive prenatal testing (NIPT) in screening for fetal chromosomal diseases. Methods A retrospective analysis was performed on NIPT results, prenatal diagnoses, and pregnancy outcomes of early pregnant women with enlarged NT at our center from 01/07/2018 to 01/01/2021. To ensure data integrity and minimize extraction bias, phased data access was adopted: the first batch of data was extracted from 01/07/2019 (start of Phase 1) to 20/07/2019 (end of Phase 1), covering participants examined from 01/07/2018 to 30/06/2019; the second batch was extracted from 01/02/2020 (start of Phase 2) to 20/02/2020 (end of Phase 2), including participants examined from 01/07/2019 to 01/01/2020. Chi-square tests were used to compare the incidence of fetal chromosomal abnormalities between the enlarged NT and normal NT groups, as well as among the subgroups of enlarged NT. Results Out of 48,130 women screened by NIPT, 774 had enlarged NT (≥2.5 mm); among these, 85 were classified as high-risk, and 72 underwent invasive diagnosis, resulting in 64 positive cases (including 42 cases of trisomy 21, among others). The thickening of NT was correlated with a higher detection rate of abnormalities, which was statistically significant. Among the 689 cases of enlarged NT with low-risk NIPT results, 20 were lost to follow-up, 5 terminated their pregnancies, while the others had healthy live births. Conclusion Early pregnancy NT combined with NIPT demonstrates a high predictive value for fetal chromosomal abnormalities and holds significant importance for clinical pregnancy guidance.